Examining a servant leadership construct and its influence on organizational citizenship behavior - Diah Astrini Amir; Claudius Budi Santoso (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2019)
This study aims to test a servant leadership construct, the Servant Leadership Survey (SLS), in the context of a collective culture. It also examines the effect of each servant leadership (SL) dimension on the organizational citizenship behavior (OCB) of employees. This study uses a validatory factor analysis method to examine the consistency of the SLS construct and, using a purposive sampling approach, involves 295 respondents working in profit and non-profit organizations. The results of this study reveal that only six dimensions of the eight-dimensional SL accord with the context of collective culture. The six dimensions are empowerment, standing back, forgiveness, courage, authenticity, and humility. The study also reports that the dimensions of standing back and authenticity have an effect on individual OCB, while the dimensions of empowerment and standing back affect organizational OCB. This study contributes to understanding different cultural contexts (individualistic versus collective) and the requirement to adjust the SL dimensions. These dimensions have different effects on OCB at the individual and organizational levels.